4 ALDOSTERONE AND CORTISOL: IS THERE A COMMON STIMULUS IN SUBJECTS WITH RESISTANT HYPERTENSION?. Issue 1 (1st January 2007) - Gaddam, K. K.; Pimenta, E.; Pratt-Ubunama, M. N.; Nishizaka, M. K.; Aban, I.; Oparil, S.; Calhoun, D. A.
Abstract : Background: Resistant hypertension defined as blood pressure (BP) > 140/90 mm Hg on three antihypertensive agents is a common problem. It has been reported from centers worldwide that these patients have a near 20% prevalence of primary aldosteronism (PA). The etiology of the high prevalence of hyperaldosteronism in this high-risk group is unknown. The purpose of current study is to characterize resistant hypertensive patients and identify potential stimuli of aldosterone secretion in subjects with resistant hypertension. Methods: Consecutive subjects referred for resistant hypertension and control subjects with normal or mildly elevated blood pressure were prospectively evaluated with plasma aldosterone concentration (PAC), plasma renin activity (PRA), brain natriuretic peptide (BNP), atrial natriuretic peptide (ANP), and a 24-hour urine collection for aldosterone (Ualdo), creatinine, protein, cortisol (UCort), sodium (UNa), and potassium (UK) during a normal diet. All hypertensive subjects were on a stable antihypertensive regimen. Results: 290 resistant hypertensive subjects and 53 controls were evaluated. Age (54.51 ± 10.83 vs 50.36 ± 10.15, p = .01), clinic BP (145 ± 21/85 ± 15 vs 125 ± 10/79 ± 7 mm Hg), PAC (13.07 ± 9.3 vs 8.44 ± 5.17 ng/dL, p = .0005), Ualdo (12.79 ± 9.98 vs 9.73 ± 6.58 μg/24 h, p = .033), BNP (41.49 ± 47.79 vs 22.48 ± 24.74 pg/mL, p = .0069), ANP (105.60 ± 76.51 vs 49.87 ± 16.65, p = .008) were higher in resistant hypertensive subjects compared with controls. BMI and waist and neck circumference were similar. A multivariate regression analysis with age, sex, race, BMI, Una, and UCort as covariates predicting aldosterone secretion shows that UCort is the strongest predictor of UAldo ( p = .012). The R 2 for this model is 17.4%. Subgroup analysis further showed that resistant hypertensive subjects with high UAldo (> 12 μg/24 h, n = 68), UCort (103.95 ± 40.51 vs 77.75 ± 42.94, p = .0004), UNa (200.34 ± 94.79 vs 172.96 ± 75.20 mEq/24 h, p = .0072), and UK (80.44 ± 33.79 vs 49.49 ± 20.62, p < .0001) were higher compared with subjects with normal or low UAldo. Conclusion: Our findings indicate a state of hyperaldosteronism and in spite of diuretic use, persistent intravascular volume expansion evident from a high BNP and ANP values in subjects with resistant hypertension. These findings also suggest that in these subjects, there may be a common stimulus for cortisol and aldosterone such as ACTH, other stimuli being dietary sodium and/or dietary potassium.